Options of Funding and Ethical Clearance for Medical Researchers in India - Das, Semanti; Chandra, Ankit; Nongkynrih, Baridalyne (Annals of the National Academy of Medical Sciences (India), 2023)
Research forms an integral part of present world development and interest. It is the primary source of speculation and outcome-based decision making. Medical research work proves to be a big challenge in low- and middle-income countries due to the constraint of resources and capacity building. The disparities in the distribution of resources, inadequate policy implementation, and lack of prioritization of research make the research challenging. There has been an increase in medical research in India but it is not adequate when compared to other countries or areas. Medical researchers face multiple issues, mainly funding and ethical approval and are stunted by the unacceptance in high-indexed journals. In this paper, we have compiled the options for funding and ethical options and ways available for researchers in India. This will help and encourage researchers pro-actively by providing some guidance on the issues related to finance and ethics required for conducting scientific research.
Keywords: Medical Research; challenges; ethical clearance; funding